THE SPECIES COMPOSITION OF POISONOUS MARINE PRODUCTS THAT CAN CAUSE A NUMBER HUMAN DEATHS IN THE COASTAL WATERS OF SOUTHERN CENTRAL VIETNAM - Phung, Nguyen Huu; Hoa, Tran Thi Hong; Van, Tran Thi Le; Ho, Dao Tan; Du, Pham Thi; Nguyen, Cao Van (Vietnam Journal of Marine Science and Technology, 2008)
The study was carried out during the period from June, 2003 to October, 2004 in the coastal waters of southern central Vietnam (from Da Nang city to Vung Tau city). There were 39 species of poisonous marine products that can causes a number human deaths. They belonging to three Phyla: Mollusca: 3 species: (Cephalopoda: I species: Greater blue-ringed octopus (Hapalochaena lunulata Q. & G., 1832); Gastropoda: 2 species: Geographus conus snail (Conus geograpus L., 1758) and Textile conus snail (onus textile L., 1758), Arthropoda: 4 species: (Crustacea: 3 species: Devil crabs (Zosimus aeneus L., 1958); Floridus crabs (Atergastis floridus L., 1758); (Platrpodia granulosa Ruppell, 1830); Merostomata: 1 horseshoe crabs (Carcinoscorpius rotundicauda Latreille, 1826) and Vertebrata 32 species: Snapper: 1 species: Two-spot red snapper (Lutjanus bohar Forskal, 1775); Goby: 1 species: Shadow goby (Yongeichthys ne bulosus Forskal, 1775), mainly 21 species puffer of family Tetraodontidae. The Reptilia are 9 species sea snake of subfamily Hydrophinae